Santri dan Gudig: Studi Analisis Pendidikan dan Kesehatan di Pondok Pesantren Kabupaten Tegal - Hasan Mutawakil Billah; Diana Amalia; Baeni Abdul Fatah; Irvan Rosyady; Zidni Ilman Nafi’ (La-Tahzan: Jurnal Pendidikan Islam, 2023)
Gudik or its Latin name Scabies is a skin disease characterized by intense itching and caused by a small tick called sarcoptes scabiei. These fleas/bacteria secrete saliva, eggs and feces. gudig or scabies infects most students/students who live in dormitories or boarding schools, this can be caused by several possibilities including lack of personal hygiene, starting from body hygiene to the clothes they wear every day. This research is field research with a case study, namely a study conducted at the Tarbiyatul Mubtadiin Danawarih Islamic Boarding School, Balapulang Subdistrict, a place chosen as a location to investigate objective symptoms that occur at that location. The approach taken is a qualitative approach and the data collection techniques of this research are observation, interview and documentation. The results of this study show that: 1. This secabies disease mostly attacks new students, but it does not rule out the possibility that old or senior students are also affected by sacabies 2. Scabies among the boarding school also does not affect these students to continue to study diligently because the students at the Tarbiyatul Mubtaidiin Islamic Boarding School believe that scabies or gudig disease is one of the tests that must be passed.